Numerical modeling and simulation of the behavior of non-engineered reinforced concrete slabs - Vasquez, Renz B.
Natural calamities like earthquake, typhoons and tsunamis may cause massive loss of lives and failure of numerous structure. In developing countries like the Philippines, most of the collapsed structures are found to be non-engineered structures. Performance of non-engineered building and its components must be analyzed in order to ensure safety and serviceability to occupants and/or users. This study focuses on the behavior of non-engineered reinforced concrete (RC) slabs in the Philippines. Important design parameters of non-engineered RC slabs were determined and analyzed through a survey with 34 construction workers as respondents. The most adjusted design parameters are concrete strength, rebar spacing, slab thickness, rebar size and rebar position. The behavior of non-engineered RC slab was investigated through numerical modeling and simulation with varying design parameters, gravity load magnitude and length-to-width ratios using SAP2000. Equations of proportionality were generated by observing the trends of simulation results. Numerical examples of typical slabs show that the change in deflection, bending moment and stresses follow the expected trend with the changes in concrete strength, slab thickness and rebar position while change in rebar size and rebar position follow expected trend on larger loads. Thickness and concrete strength greatly affects deflection and stresses.